La prédiction des contacts avec le tribunal de la jeunesse : utilisation de l’évaluation du comportement par les pairs au début de l’école primaire - Tremblay, Richard; Desmarais-Gervais, Lise; LeBlanc, Marc; Schwartzman, Alexandre (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1986)
This study sets out to verify to what extent the evaluations of the behaviour of children by their peers in first year primary school make it possible to predict those who will eventually end up with an open record at the Juvenile Court. During their first year at school the children are classified according to the following categories : aggressive, socially withdrawn, aggressive-withdrawn, neither aggressive/nor withdrawn (contrast). A total of 992 subjects (493 girls and 499 boys) were evaluated at two different times during the study. The results indicate that the “aggressive-withdrawn” subjects, among the girls, are more likely to have an open record at the Court during the 7 or 8 years after having been evaluated in first year primary school. These findings may indicate that the girls whose behaviour is aberrant are more easily identified by their peers, given the fact that they generally have fewer problems of adaptation than the boys during their first year of school.